Influence of Organizational Culture & Workload On The Performance Of ASN Employees in The Directorate General of Immigration in The Directorate of Visas & Travel Documents With Work Motivation as an Intervening Variable - Imam Prawira; Yayan Hadiyat; Radjab Tampubolon (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
workload on the performance of ASN employees in the Visa and Travel Documents Directorate of the Directorate General of Immigration, with work motivation as an intervening variable. The approach used is quantitative with a causal-descriptive design, and the entire population of 94 people was sampled through census technique. Data were collected through closed questionnaires and analyzed using the Structural Equation Modeling method with the help of SmartPLS 4.1.1.4. The research results show that organizational culture has a positive and significant impact on work motivation and employee performance, both directly and indirectly. Conversely, workload has a negative and significant impact on work motivation, but does not significantly and directly affect employee performance. Work motivation has been proven to play a significant mediating role in the relationship between organizational culture and performance, as well as between workload and employee performance. The research model has a high goodness of fit value, with strong predictive capability. The research results emphasize the importance of strengthening a positive organizational culture and managing a balanced workload to enhance employee motivation and performance sustainably